Suitability mapping of native tree species in dry-hot valleys of Yunnan based on InVEST-MaxEnt coupled modeling: model validation framework with native tree species actual distribution and seed germination - Xie, Meng; Song, Xiaobo; Zhang, Xuexing; Ma, Yongpeng; Song, Zhilin; Li, Fengjuan; Li, Wei; Fan, Linyuan; Ma, Hong (Frontiers in Plant Science, 2025)
IntroductionThe target valleys along the Jinsha, Nujiang, Lancang, and Yuanjiang Rivers exhibit acute human-land conflicts and ecosystem vulnerability. Predicting the distribution of potential suitable habitats for native tree species in Yunnan Province provides basin-scale insights for the management of ecosystems in dry and hot valleys, thereby advancing restoration planning in dry-hot valleys.MethodsThis study investigates native tree species suitability in Yunnan’s dry-hot valleys using an integrated MaxEnt-InVEST modeling framework.ResultsTemperature and precipitation emerged as dominant bioclimatic controls, with optimal species occurrence (1 000–2 500 m) showing negative elevation correlation. Four native tree species (Osteomeles schwerinae, Phyllanthus emblica, Quercus francetii and Sapindus delavayi) displayed fragmented suitable areas along mountainous riparian zones, while habitat quality hotspots mainly covered non-urbanized regions, avoiding central urban clusters and northeastern/southeastern karst zones. The coupled model demonstrated significantly improved accuracy compared to the standalone MaxEnt by incorporating land-use impacts, with Yuanmou County case analysis confirming the enhanced predictive capability through actual distribution patterns. Spatial prioritization identified core planting clusters in central/southeastern valleys, though fragmented by agricultural encroachment.DiscussionThis methodology provides a cost-effective solution for vegetation restoration planning in ecologically fragile dry-hot ecosystems. The research results can provide scientific support for the restoration of degraded ecosystems in dry-hot valleys of Yunnan Province, the national Afforestation program and soil and water conservation projects.